Water-based magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite and its preparation method and use
By growing nickel hydride particles using chemical bath method on the surface of carbon nanotubes, forming nickel hydride/carbon nanotube composite materials, the problem of insufficient stability and magnesium ion transport capability of water-based magnesium ion batteries is solved, and high electrochemical performance and high capacity battery performance are achieved.
Patent Information
- Application Number
- JP2024526884
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-01-17
- Filing Date
- 2023-03-31
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-03-31
AI Technical Summary
It is difficult to find suitable cathode materials for water-based magnesium ion batteries in the prior art. Especially under the small size of magnesium ions, high charging density and strong polarization, the stability and magnesium ion transport capability of the cathode materials are insufficient, resulting in poor battery performance.
Ni-hydride particles are grown on the surface of carbon nanotubes by chemical bathing to form a nickel hydride/carbon nanotube composite material as the positive electrode material for water-based magnesium ion batteries. This method is simple, safe, environmentally friendly, and can evenly distribute nickel hydride particles to improve the electrochemical performance of the battery.
It has achieved high electrochemical cycling stability and magnesium ion storage capacity of nickel hydride/carbon nanotube composites in water-based magnesium ion batteries, and has high capacity (about 135mAh·g-1) and a flat charging and discharging platform (about 0.58V), which greatly improves the performance of the battery.
Smart Images

Figure 2025511422000001_ABST
Abstract
Description
[Technical field]
[0001] (Related Applications) This application claims priority to a Chinese patent application filed on January 17, 2023, application number 202310066012.3, and title "Water-based magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite and preparation method thereof, and use thereof."
[0002] (Technical field) The present application relates to the technical field of inorganic nanomaterials, in particular to a water-based magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite and its preparation method and application. [Background technology]
[0003] In recent years, as an intermediate step to realize the integrated, clean and efficient use of energy, energy storage has attracted widespread attention from researchers around the world. In particular, with the large-scale grid connection of renewable energy sources with stochastic and fluctuating properties, and the large-scale access of interactive devices such as electric vehicles and distributed power sources, the power system will be characterized by a high proportion of renewable energy sources and a high proportion of power electronics. In order to realize the load balance of the new power system centered on new energy sources, energy storage technology plays an important role. However, traditional energy storage systems such as supercapacitors, lithium-ion batteries, and flow batteries have safety risks and are also expensive. As a result, aqueous batteries have emerged. Compared with many aqueous batteries, magnesium has the characteristics of abundant resources, low price, non-toxic or low-toxicity compounds, and safety. The aqueous magnesium-ion battery has the advantages of being green, low cost, and high safety. By utilizing multiple electron transfer pathways during the charging and discharging process, high energy density and power density can be achieved, and it is expected to become one of the next generation of important energy storage devices. However, due to the small size of magnesium ions, high charge density, and strong polarization, it is more difficult to form embedded compounds. Therefore, the options for positive electrode materials for magnesium ion batteries are limited, and most electrode materials have poor diffusion and kinetic properties of magnesium ions, which limits the transport capacity of magnesium ions in the electrode materials, affecting the multiplication performance of the battery, making it difficult to achieve the desired multiplication performance as well as the theoretical capacity. Therefore, the research and development of positive electrode materials is crucial for the development and application of aqueous magnesium ion batteries.
[0004] Currently, the main research direction for positive electrode materials is to find materials that can allow reversible insertion / extraction of magnesium ions during charging / discharging and can be stabilized in the electrolyte.
[0005] Alkaline electrolytes are usually corrosive, corroding metal-based anodes and resulting in poor electrochemical stability. In addition, electrolyte leakage is likely to cause safety issues, hindering large-scale application. Compared with alkaline batteries, neutral batteries have superior safety and the neutral electrolyte is less corrosive, making them the best choice among aqueous batteries. Meanwhile, among the many cathode materials, transition metal oxides, such as manganese- and vanadium-based, have been the main research subjects due to their advantages of low cost and high capacity. Nickel-based compounds are rarely used as battery cathode materials, especially aqueous magnesium-ion cathode materials, due to their high conversion potential between divalent nickel ions and trivalent nickel ions and their small window of electrochemical stability in aqueous electrolytes. Nickel-based compounds are generally used as anode materials for lithium batteries, and as a cathode material for nickel-based batteries, they are one of the most widely studied cathode materials due to their advantages of easy availability of raw materials, low price, and environmental friendliness. However, nickel hydroxide positive electrodes have the disadvantages of low specific capacity, poor cycle stability, and low utility as a positive electrode material for nickel-based batteries, because the negative electrode material continues to deposit on the surface during charging and discharging, blocking the mass transfer pathway in the liquid phase and poisoning the positive electrode, causing the battery to fail. In particular, when used as a positive electrode material for an aqueous magnesium ion battery, nickel-based compounds cannot be used as a positive electrode material for an aqueous magnesium ion battery, due to the disadvantages of small magnesium ion volume, high charge density, and formation of buried compounds.
[0006] In Non-Patent Document 1, Wang Xiaofeng et al. disclose that a composite electrode obtained by depositing nickel oxide on the surface of a carbon nanotube by an electrochemical method and a supercapacitor using the composite electrode have good reversibility and improved performance of nickel oxide. Patent Document 1 discloses a carbon nanotube-lithium titanium doped nickel oxide compound and a preparation method thereof, which is a compound obtained by grafting lithium titanium doped nickel oxide by a surface carboxylation method of a carbon nanotube, and prepares a material having both a high dielectric constant and low dielectric loss. However, all of the above disclosed technologies have problems such as complicated processing techniques and high manufacturing costs. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] China Patent Application Publication No. 103131211 [Non-patent literature]
[0008] [Non-Patent Document 1] "Electrochemical behavior of nickel oxide deposited on the surface of carbon nanotubes and its supercapacitor", Journal of Inorganic Chemistry Vol.18, No.2, March 2003. Summary of the Invention [Problem to be solved by the invention]
[0009] The present application provides an aqueous magnesium ion battery positive electrode material, nickel hydroxide / carbon nanotube composite, its preparation method and use, which is an aqueous magnesium ion battery positive electrode material made of a high valent nickel-based compound and carbon nanotubes, and the preparation method is mild, the operation is simple, it is safe and environmentally friendly, the structure is stable and the electrochemical performance is excellent. [Means for solving the problem]
[0010] In order to achieve the above objectives, the present application provides the following technical solution, which is a method for preparing a water-based magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite, comprising: using carbon nanotubes as a substrate, growing nickel hydroxide particles on the surface of the carbon nanotubes by a chemical bath method, so that the nickel hydroxide is uniformly distributed on the surface of the carbon nanotubes to prepare a nickel hydroxide / carbon nanotube composite; and by this method, the nickel hydroxide is uniformly distributed on the surface of the carbon nanotubes to form a compound having nickel hydroxide / carbon nanotubes.
[0011] Preferably, the process steps of the chemical bath method include: S1. Mix nickel sulfate hexahydrate, potassium persulfate and deionized water and stir evenly to form a uniform seed layer solution; S2. Add ammonium hydroxide drop by drop into the seed layer solution, stir evenly, and react completely to obtain a precursor solution; S3. Add carbon nanotubes to the precursor solution, stir evenly, react for 20-30 minutes, and dry to obtain the nickel hydroxide / carbon nanotube composite, where the carbon nanotubes are pretreated before use, and include washing the carbon nanotubes with water and / or ethanol solution, and drying at 50-70°C in a blower drying box for 30-60 minutes.
[0012] In the above steps, divalent nickel is oxidized to higher trivalent nickel by potassium persulfate, a strong oxidizing agent, and converted into nickel hydroxide under alkaline conditions. The nickel hydroxide / carbon nanotube composite is then deposited on the surface of the carbon nanotube through hydrogen bonding.
[0013] Preferably, in S1, the mass ratio of nickel sulfate hexahydrate to potassium persulfate in the seed layer solution is (7-8):(3-4).
[0014] Preferably, in S2, the concentration of ammonium hydroxide dropped into the precursor solution is 28 wt %, and the volume ratio of ammonium hydroxide to the seed layer solution is 1:10-30.
[0015] Preferably, in S3, after the reaction is completed, the drying step includes placing the carbon nanotubes in a ventilation drying box at 50 to 70° C. and holding the carbon nanotubes for 30 to 90 minutes to obtain the nickel hydroxide / carbon nanotube composite.
[0016] Preferably, in S1-S3, the reaction conditions are a temperature of 25 to 35° C. and a rotation speed of 500 to 1000 rpm for uniform stirring.
[0017] In general, nickel hydroxide, a nickel-based compound, can be widely used as an alkaline electrolyte electrode material for energy storage and conversion. Nickel hydroxide is a common inorganic compound with a layered structure of nickel-based compounds, and has the advantages of simple preparation process, low toxicity, and high redox activity. Nickel hydroxide is converted from nickel hydroxide by oxidative dehydrogenation reaction, during which the presence of oxygen vacancies and more defects help provide reactive sites, increase the adsorption capacity of hydrated magnesium ions, and provide sufficient reactivity for embedding magnesium ions. In addition, the defects and vacancies in nickel hydroxide are also favorable for composite with less hydrophilic carbon substrates, which increases the electrical conductivity of the composite and further improves the reaction rate.
[0018] The nickel hydroxide / carbon nanotube composite prepared by using the above technical solution in this application uses carbon nanotubes as a substrate, high valent nickel-based compound as a seed layer, and grows nickel hydroxide particles on the surface of carbon nanotubes by chemical bath method to prepare nickel hydroxide / carbon nanotube composite, and nickel hydroxide is uniformly distributed on the surface of carbon nanotubes. In this application, a strong oxidizing agent is used to convert low valent nickel into a stable high valent nickel-based compound, and the prepared nickel hydroxide / carbon nanotube composite is used as a working electrode, platinum wire and silver / silver chloride are used as counter and reference electrodes, respectively, and applied to an aqueous magnesium ion battery with 1M magnesium chloride aqueous solution as an electrolyte. The electrochemical signal test shows that it has excellent cycle stability and excellent magnesium ion storage capacity.
[0019] The embodiments of the present application further provide a nickel hydroxide / carbon nanotube composite, which is obtained by using the above-mentioned method for preparing an aqueous magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite, and the nickel hydroxide is uniformly distributed on the surface of the carbon nanotube, forming the above-mentioned nickel hydroxide / carbon nanotube composite.
[0020] The embodiments of the present application further provide a water-based magnesium ion positive electrode material, which includes the nickel hydroxide / carbon nanotube composite or the nickel hydroxide / carbon nanotube composite prepared by the above preparation method.
[0021] An embodiment of the present application further provides an aqueous magnesium ion battery comprising the aqueous magnesium ion positive electrode material.
[0022] Furthermore, embodiments of the present application further provide an electrochemical energy storage device comprising the water-based magnesium ion positive electrode material, or an water-based magnesium ion battery. Effect of the Invention
[0023] The technical solution of this application has the following technical effects:
[0024] 1. According to the technical solution of this application, nickel hydroxide nanoparticles are synthesized on the surface of carbon nanotubes by a simple chemical bath method, and the nickel hydroxide nanoparticles are deposited on the surface of carbon nanotubes to form a nickel hydroxide / carbon nanotube composite, which is used as the positive electrode material of an aqueous magnesium ion battery. It has excellent electrochemical cycle stability and magnesium ion storage capacity. In a 1M magnesium chloride electrolyte solution, the nickel hydroxide / carbon nanotube composite has a high capacity (about 135 mAh g -1 ) and a flat charge-discharge plateau (approximately 0.58 V vs. Ag / AgCl).
[0025] 2. The water-based magnesium ion positive electrode material provided in the technical solution of this application The high valent nickel-based compound has the advantages of being safe and environmentally friendly, having a stable structure, a gentle preparation method, and simple operation.
[0026] 3. The technical solution of this application applies nickel-based compounds to aqueous magnesium ion batteries, which broadens the selection range of aqueous magnesium ion battery positive electrode materials, and has the advantages of easy availability of raw materials, low cost and environmental friendliness. [Brief description of the drawings]
[0027] [Figure 1] FIG. 2 is a schematic XRD diagram of the nickel hydroxide / carbon nanotube composite prepared in Example 1 of the present application. [Figure 2a] 1 is a low magnification SEM photograph of the nickel hydroxide / carbon nanotube composite prepared in Example 1 of the present application. [Figure 2b] 1 is a high magnification SEM photograph of the nickel hydroxide / carbon nanotube composite prepared in Example 1 of the present application. [Figure 3a] 1 is a linear cyclic voltammogram of carbon nanotubes and nickel hydroxide / carbon nanotube composite prepared in Example 1 of the present application. [Figure 3b]FIG. 2 is a charge / discharge performance diagram of the carbon nanotubes and nickel hydroxide / carbon nanotube composite prepared in Example 1 of the present application. [Figure 4a] FIG. 2 shows the charge / discharge and rate performance diagrams of the carbon nanotubes and nickel hydroxide / carbon nanotube composite prepared in Example 1 of the present application in different electrolytes. [Figure 4b] FIG. 2 is a rate performance diagram of the carbon nanotubes and nickel hydroxide / carbon nanotube composites prepared in Example 1 of the present application in different electrolytes. [Figure 5a] FIG. 2 is a rate performance diagram of carbon nanotubes and nickel hydroxide / carbon nanotube composites prepared in Example 1 of the present application in 1 M magnesium chloride solution. [Figure 5b] FIG. 2 shows the cycling stability of carbon nanotubes and nickel hydroxide / carbon nanotube composites prepared in Example 1 of the present application in 1 M magnesium chloride solution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] In order to make the objectives, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions of the embodiments of the present application are described clearly and completely, but obviously, the described embodiments are only some embodiments of the present application, not all embodiments. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative labor should all be included in the protection scope of the present application.
[0029] The present application provides a water-based magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite and its preparation method and application, in which carbon nanotubes are used as a substrate, and nickel hydroxide particles are grown on the surface of the carbon nanotubes by a chemical bath method to prepare a nickel hydroxide / carbon nanotube composite.
[0030] The chemical bath method includes the following: mix nickel sulfate hexahydrate, potassium persulfate and water, stir evenly to form a uniform seed layer solution, add ammonium hydroxide drop by drop to the seed layer solution, stir evenly and react completely to obtain a precursor solution, finally add carbon nanotubes to the precursor solution, stir evenly, uniformly deposit nickel hydroxide particles on the surface of the carbon nanotubes, react for 20-30 minutes, and dry to obtain a nickel hydroxide / carbon nanotube composite.
[0031] The technical solutions of the present application are described in further detail below through specific examples.
[0032] [Example 1] This embodiment provides a water-based magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite and its preparation method and application, which includes the following specific steps:
[0033] (1) Preparation of nickel hydroxide / carbon nanotube composite electrode: Carbon nanotubes are used as substrates, and nanostructured nickel hydroxide particles are grown on their surface using a simple and mild chemical bath method.
[0034] Specifically, an appropriate amount of deionized water and anhydrous ethanol solution are taken to surface treat the carbon nanotubes, and then the sample is placed in a blast drying box at 50°C for 40 min. An appropriate volume of deionized water is taken, and nickel sulfate hexahydrate with a volume concentration of 100 mg / mL and potassium persulfate with a volume ratio of 40 mg / mL are added in a volume ratio of 1:2, and stirred uniformly for 10 min to form a seed layer solution. 28 wt% ammonium hydroxide is added drop by drop to the seed layer solution, and the volume ratio of ammonium hydroxide to the seed layer solution is 1:10, and stirred at room temperature for 2 min to form a precursor solution. An appropriate amount of carbon nanotubes is added to the precursor solution, and stirred uniformly at room temperature for 20 min. After the reaction is completed, the sample is suction filtered, and placed in a blast drying box at 50°C for 30 min to obtain the structure of nickel hydroxide / carbon nanotube composite.
[0035] 1, which is a schematic XRD diagram of the nickel hydroxide / carbon nanotube composite prepared in step (1) of this example. Compared with the XRD characteristic peaks of carbon nanotubes, the main characteristic peaks of the nickel hydroxide / carbon nanotube composite are located at 13.4°, 33.9° and 42.2°, respectively, indicating that the nickel hydroxide / carbon nanotube composite has been successfully prepared.
[0036] Referring to Figures 2a and 2b, these are low-magnification SEM photographs (Figure 2a) and high-magnification SEM photographs (Figure 2b) of the nickel hydroxide / carbon nanotube composite prepared in step (1) of this Example, in which nickel hydroxide nanoparticles are distributed on the surface of the carbon nanotubes.
[0037] (2) Testing of the nickel hydroxide / carbon nanotube composite electrode: The prepared nickel hydroxide / carbon nanotube composite was used as the working electrode, a platinum wire and a silver / silver chloride were used as the counter and reference electrodes, respectively, and a 1M magnesium chloride aqueous solution was used as the electrolyte to perform an electrochemical signal test of the three-electrode system. In a 1M magnesium chloride aqueous solution, the capacity of the nickel hydroxide / carbon nanotube composite was approximately 135 mAh g -1 , the discharge plateau was about 0.58V.
[0038] Referring to Figures 3a and 3b, which are the linear cycle voltammogram and charge / discharge performance diagram of the nickel hydroxide / carbon nanotube composite prepared in step (1) of this example, respectively, the linear cycle voltammogram curve of the nickel hydroxide / carbon nanotube composite shows obvious redox peaks, which confirms that the electrochemical behavior of magnesium ion embedment / de-embedding can occur therein, and the charge / discharge performance diagram further shows that it has high capacity and discharge plateau.
[0039] 4a and 4b are charge / discharge and rate performance diagrams of the nickel hydroxide / carbon nanotube composite prepared in step (1) in different electrolytes, respectively. As can be seen from the comparison of the diagrams, the nickel hydroxide / carbon nanotube composite shows a high discharge plateau and excellent cycle stability in 1M magnesium chloride electrolyte compared with 1M potassium hydroxide electrolyte.
[0040] 5a and 5b are graphs showing the rate performance and cycle stability of the nickel hydroxide / carbon nanotube composite prepared in step (1) of this example in 1 M magnesium chloride solution, respectively. After 200 cycles, the capacity of the nickel hydroxide / carbon nanotube composite retained about 97% of the initial capacity.
[0041] [Example 2] This example provides a method for preparing a nickel hydroxide / carbon nanotube composite electrode, which includes the following specific steps:
[0042] (1) Preparation of nickel hydroxide / carbon nanotube composite electrode: Carbon nanotubes are used as substrates, and nanostructured nickel hydroxide particles are grown on their surface by a simple and mild chemical bath method.
[0043] Specifically, an appropriate amount of deionized water and anhydrous ethanol solution are taken to surface treat the carbon nanotubes, and then the carbon nanotubes are placed in a ventilated drying box at a drying temperature of 50°C for 40 min. An appropriate volume of deionized water is taken, and nickel sulfate hexahydrate with a volume concentration of 100 mg / mL and potassium persulfate with a volume ratio of 40 mg / mL are added in a volume ratio of 1:1.5, and the seed layer solution is formed by uniformly stirring for 10 min. 28 wt% ammonium hydroxide is added drop by drop to the seed layer solution, and the volume ratio of ammonium hydroxide to the seed layer solution is 1:10, and the precursor solution is formed by stirring at room temperature for 2 min. An appropriate amount of carbon nanotubes is added to the precursor solution, and the precursor solution is uniformly stirred at room temperature for 30 min. After the reaction is completed, the sample is suction filtered, and placed in a ventilated drying box at 50°C for 30 min to obtain the structure of nickel hydroxide / carbon nanotube composite.
[0044] (2) Testing of the nickel hydroxide / carbon nanotube composite electrode: The prepared nickel hydroxide / carbon nanotube composite was used as the working electrode, a platinum wire and a silver / silver chloride were used as the counter and reference electrodes, respectively, and a 1M magnesium chloride aqueous solution was used as the electrolyte to perform an electrochemical signal test of the three-electrode system. In a 1M magnesium chloride aqueous solution, the capacity of the nickel hydroxide / carbon nanotube composite was approximately 132 mAh g -1 The discharge plateau was about 0.58 V. After 200 cycles, the capacity of the nickel hydroxide / carbon nanotube composite was retained at about 95% of the initial capacity.
[0045] [Example 3] This embodiment further provides a method for preparing a nickel hydroxide / carbon nanotube composite electrode, which includes the following specific steps:
[0046] (1) Preparation of nickel hydroxide / carbon nanotube electrode: Carbon nanotubes are used as substrates, and nanostructured nickel hydroxide particles are grown on their surface by a simple and mild chemical bath method.
[0047] Specifically, an appropriate amount of deionized water and anhydrous ethanol solution are taken to surface treat the carbon nanotubes, and then the carbon nanotubes are placed in a ventilated drying box at a drying temperature of 50°C for 40 min. An appropriate volume of deionized water is taken, and nickel sulfate hexahydrate with a volume concentration of 100 mg / mL and potassium persulfate with a volume ratio of 40 mg / mL are added in a volume ratio of 1:2, and the seed layer solution is formed by uniformly stirring for 10 min. 28 wt% ammonium hydroxide is added drop by drop to the seed layer solution, and the volume ratio of ammonium hydroxide to the seed layer solution is 1:10, and the precursor solution is formed by stirring at room temperature for 2 min. An appropriate amount of carbon nanotubes is added to the precursor solution, and the solution is uniformly stirred at room temperature for 40 min. After the reaction is completed, the sample is suction filtered, and placed in a ventilated drying box at 50°C for 30 min to obtain the structure of nickel hydroxide / carbon nanotube composite.
[0048] (2) Testing of the nickel hydroxide / carbon nanotube composite electrode: The prepared nickel hydroxide / carbon nanotube composite was used as the working electrode, a platinum wire and a silver / silver chloride were used as the counter and reference electrodes, respectively, and a 1M magnesium chloride aqueous solution was used as the electrolyte to perform an electrochemical signal test of the three-electrode system. In a 1M magnesium chloride aqueous solution, the capacity of the nickel hydroxide / carbon nanotube composite was approximately 134 mAh g -1 The discharge plateau was about 0.58 V. After 200 cycles, the capacity of the nickel hydroxide / carbon nanotube composite was retained at about 96% of the initial capacity.
[0049] [Comparative Example] This comparative example provides a method for preparing a nickel hydroxide electrode, which includes the following specific steps:
[0050] (1) Preparation of nickel hydroxide electrode: Nanostructured nickel hydroxide is similarly grown and prepared by a simple and mild chemical bath method.
[0051] Take an appropriate amount of deionized water, add nickel sulfate hexahydrate with a volume concentration of 100 mg / mL, and stir evenly for 10 minutes to form a seed layer solution. Add 28 wt% ammonium hydroxide drop by drop to the above seed layer solution, and the volume ratio of ammonium hydroxide to seed layer solution is 1:10, and stir at room temperature for 4 hours. After the reaction is completed, the sample is suction filtered and placed in a 50°C air drying box for 30 minutes to obtain nanostructured nickel hydroxide.
[0052] (2) Test of nickel hydroxide electrode: The prepared nickel hydroxide was used as the working electrode, platinum wire and silver / silver chloride as the counter and reference electrodes, respectively, and a three-electrode electrochemical signal test was performed using 1M magnesium chloride aqueous solution as the electrolyte. In the 1M magnesium chloride aqueous solution, nickel hydroxide did not show any chemical signal peak, indicating that nickel hydroxide has no electrochemical magnesium storage ability.
[0053] As can be seen from the above examples, when the nickel hydroxide / carbon nanotube composite prepared in this application is applied as a working electrode to an aqueous magnesium ion battery, it has excellent electrochemical cycle stability and magnesium ion storage capacity, and in a 1M magnesium chloride electrolyte solution, the nickel hydroxide / carbon nanotube composite has a high capacity (132-135 mAh g -1 ) and a flat charge / discharge plateau (approximately 0.58 V vs. Ag / AgCl).
[0054] As can be seen from the comparison between Examples 1 to 3 and the Comparative Examples, the nickel hydroxide / carbon nanotube composite prepared by the technical solution of the present application overcomes the technical problem in the prior art that nickel hydroxide cannot be applied as a working electrode in aqueous magnesium ion batteries, and as can be seen from the results of Examples 1 to 3, when the nickel hydroxide / carbon nanotube composite prepared by the technical solution of the present application is applied to aqueous magnesium batteries, it has excellent electrochemical cycle stability and magnesium ion storage capacity.
[0055] The above are only preferred embodiments of the present application, and do not limit the scope of protection of the present application, and those skilled in the art may make various modifications and variations to the present application. As long as they do not deviate from the spirit and principles of the present application, any changes, modifications, substitutions, integrations and parameter adjustments made to these embodiments without departing from the principles and spirit of the present application through ordinary substitution or achieving the same function are all within the scope of protection of the present application.
[0056] (Additional Note) (Appendix 1) A method for preparing an aqueous magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite, comprising: using carbon nanotubes as a substrate; growing nickel hydroxide particles on the surface of the carbon nanotubes by a chemical bath method; and distributing the nickel hydroxide uniformly on the surface of the carbon nanotubes to prepare a nickel hydroxide / carbon nanotube composite.
[0057] (Appendix 2) The chemical bath process comprises: S1. Mix nickel sulfate hexahydrate, potassium persulfate and deionized water and stir evenly to form a uniform seed layer solution; S2. Add ammonium hydroxide drop by drop into the seed layer solution, stir evenly, and react completely to obtain a precursor solution; S3. The method for preparing the aqueous magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite according to appendix 1, comprising: adding carbon nanotubes to the precursor solution, stirring the solution uniformly, reacting the solution for 20 to 30 minutes, and drying the solution to obtain the nickel hydroxide / carbon nanotube composite.
[0058] (Appendix 3) The method for preparing an aqueous magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite according to appendix 2, characterized in that in S1, the mass ratio of nickel sulfate hexahydrate to potassium persulfate in the seed layer solution is (7-8):(3-4).
[0059] (Appendix 4) The method for preparing a nickel hydroxide / carbon nanotube composite described in Appendix 2, characterized in that in S2, the concentration of ammonium hydroxide dropped into the precursor solution is 28 wt%, and the volume ratio of ammonium hydroxide to the seed layer solution is 1:10-30.
[0060] (Appendix 5) The method for preparing an aqueous magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite according to appendix 2, characterized in that in S3, after completion of the reaction, the drying step includes placing the carbon nanotubes in a ventilation drying box at 50 to 70°C and holding the same for 30 to 90 minutes to obtain the nickel hydroxide / carbon nanotube composite.
[0061] (Appendix 6) The method for preparing a water-based magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite according to any one of claims 1 to 5, characterized in that in the steps S1 to S3, the reaction conditions are a temperature of 25 to 35°C and a rotation speed of 500 to 1000 rpm for uniform stirring.
[0062] (Appendix 7) A nickel hydroxide / carbon nanotube composite obtained by using the method for preparing an aqueous magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite according to any one of claims 1 to 6, wherein nickel hydroxide is uniformly distributed on the surface of the carbon nanotube, and the nickel hydroxide / carbon nanotube composite is provided.
[0063] (Appendix 8) A water-based magnesium ion positive electrode material comprising the nickel hydroxide / carbon nanotube composite according to claim 7 or the nickel hydroxide / carbon nanotube composite prepared by the preparation method according to any one of claims 1 to 6.
[0064] (Appendix 9) 9. An aqueous magnesium ion battery comprising the aqueous magnesium ion positive electrode material of claim 8.
[0065] (Appendix 10) 10. An electrochemical energy storage device comprising the aqueous magnesium ion cathode material of claim 8 or the aqueous magnesium ion battery of claim 9.
Claims
1. A method for preparing an aqueous magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite, comprising using carbon nanotubes as a substrate, growing nickel hydroxide particles on the surface of the carbon nanotubes by a chemical bath method, and distributing the nickel hydroxide uniformly on the surface of the carbon nanotubes to prepare a nickel hydroxide / carbon nanotube composite.
2. The chemical bath process comprises: S1. Mix nickel sulfate hexahydrate, potassium persulfate and deionized water and stir evenly to form a uniform seed layer solution; S2. Add ammonium hydroxide drop by drop into the seed layer solution, stir evenly, and react completely to obtain a precursor solution; S3. The preparation method of the water-based magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite according to claim 1, comprising: adding carbon nanotube to the precursor solution, stirring uniformly, reacting for 20-30 minutes, and drying to obtain the nickel hydroxide / carbon nanotube composite.
3. The method for preparing the aqueous magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite according to claim 2, characterized in that in the step S1, the mass ratio of nickel sulfate hexahydrate and potassium persulfate in the seed layer solution is (7-8):(3-4).
4. The method for preparing a nickel hydroxide / carbon nanotube composite according to claim 2, characterized in that in S2, the concentration of ammonium hydroxide dropped into the precursor solution is 28 wt%, and the volume ratio of ammonium hydroxide to the seed layer solution is 1:10-30.
5. The method for preparing the aqueous magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite according to claim 2, characterized in that in the step S3, after the reaction is completed, the drying step includes placing the carbon nanotubes in a ventilated drying box at 50 to 70°C for 30 to 90 minutes to obtain the nickel hydroxide / carbon nanotube composite.
6. The preparation method of the water-based magnesium ion positive electrode material nickel hydroxide / carbon nanotube composite according to any one of claims 1 to 5, characterized in that in the above S1 to S3, the reaction conditions are: temperature 25 to 35°C, uniform stirring rotation speed 500 to 1000 rpm.
7. A nickel hydroxide / carbon nanotube composite obtained by using the method for preparing a nickel hydroxide / carbon nanotube composite of any one of claims 1 to 6, wherein nickel hydroxide is uniformly distributed on the surface of the carbon nanotube, and the nickel hydroxide / carbon nanotube composite is provided.
8. A water-based magnesium ion positive electrode material comprising the nickel hydroxide / carbon nanotube composite of claim 7 or the nickel hydroxide / carbon nanotube composite prepared by the preparation method of any one of claims 1 to 6.
9. 10. An aqueous magnesium ion battery comprising the aqueous magnesium ion positive electrode material of claim 8.
10. 10. An electrochemical energy storage device comprising the aqueous magnesium ion positive electrode material of claim 8 or the aqueous magnesium ion battery of claim 9.
Citation Information
Patent Citations
Method for preparing compound electrode active material of nickel hydroxide / carbon nano tube
CN101635353A
Nickel-magnesium cell
JP2021073635A
Carbon nano tube-lithium titanium doped nickel oxide compound and preparation method thereof
CN103131211A